2021
DOI: 10.1177/21582440211061349
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Teacher Educators’ Research Engagement in the Reform Process of Teacher Education Institutions in Myanmar

Abstract: This study addresses how similar teacher education institutions differ in terms of teacher educators’ research engagement and what causes these differences. Underlying factors were explored by comparing teacher educators’ research engagement at two Education Colleges in Myanmar that differed in terms of the educators’ research activities. Applying the qualitative case study research design, data were drawn from a document analysis and semi-structured interviews with the college principals and teacher educators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
(62 reference statements)
2
1
0
Order By: Relevance
“…Salter and Tett (2022) clarify what lack of time means for practitioners: making choices about priorities; setting aside time to explore research and (re)conceptualising their professional identities to incorporate research. The results are also consistent with Kyaw's (2021) findings in Myanmar higher education settings. Many factors (personal, institutional, policy-related, and system-related factors) at various layers affect educators' research engagement.…”
Section: Discussionsupporting
confidence: 90%
“…Salter and Tett (2022) clarify what lack of time means for practitioners: making choices about priorities; setting aside time to explore research and (re)conceptualising their professional identities to incorporate research. The results are also consistent with Kyaw's (2021) findings in Myanmar higher education settings. Many factors (personal, institutional, policy-related, and system-related factors) at various layers affect educators' research engagement.…”
Section: Discussionsupporting
confidence: 90%
“…Like our study, a previous study showed that teachers with more teaching experience positively perceived CPD activity practices such as research (19). Personal factors such as motivation and experiences affected teachers' research engagements (31). Studies conducted before indicated that experience variation between teachers caused variation in the CPD activity practices including research (8, 32, 33).…”
Section: Factors Affecting Article Publication and Presentation Confe...supporting
confidence: 61%
“…Thus, intrinsic motivation creates teachers engaging in research actively ( Trembley et al, 2009 ). However, teachers with research experience and skills are sometimes demotivated by their perception of the discrepancy between their preferred research and the institutions that encourage them to conduct ( Kyaw, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%